Does the majority always know best? Young children's flexible trust in majority opinion - Einav, Shiri (Public Library of Science, 2014)
Copying the majority is generally an adaptive social learning strategy but the majority does not always know best. Previous work has demonstrated young children's selective uptake of information from a consensus over a lone dissenter. The current study examined children's flexibility in following the majority: do they overextend their reliance on this heuristic to situations where the dissenting individual has privileged knowledge and should be trusted instead? Four- to six- year-olds (N = 103) heard conflicting claims about the identity of hidden drawings from a majority and a dissenter in two between-subject conditions: in one, the dissenter had privileged knowledge over the majority (he drew the pictures); in the other he did not (they were drawn by an absent third party). Overall, children were less likely to trust the majority in the Privileged Dissenter condition. Moreover, 5- and 6- year-olds made majority-based inferences when the dissenter had no privileged knowledge but systematically endorsed the dissenter when he drew the pictures. The current findings suggest that by 5 years, children are able to make an epistemic-based judgment to decide whether or not to follow the majority rather than automatically following the most common view.